Tipping for charity: a field experiment in charitable giving on free walking tours - Britta Butz; Christine Harbring (Journal of Business Economics, 2021)
The following field experiment analyzes the effect of payments in a setting of shared social responsibility where charitable giving is incorporated into a pay-what-you-want scheme as a share of the payment. The field experiment involved free walking tours. Within a timeframe of 10 weeks, tours operated as usual, while every second week a Donation Week was implemented. During Donation Week, 5% of the tips were donated to a charitable organization by the tour firm. Results reveal that tips are significantly higher in the Donation Week compared to the Baseline and that the rise in tips roughly outweighs the cost of the donation payment. Thus, while tour guides' profits do not differ between treatments donations to charity may be generated additionally in Donation Week.
Keywords: C93; D49; D64; H41; 650; Pay-what-you-want; Charitable giving; Shared social responsibility; Corporate social responsibility; Field experiment